NbNAC42 and NbZFP3 Transcription Factors Regulate the Virus Inducible NbAGO5 Promoter in Nicotiana benthamiana - Ke, Yuan-Dun; Huang, Ying-Wen; Viswanath, Kotapati Kasi; Hu, Chung-Chi; Yeh, Chuan-Ming; Mitsuda, Nobutaka; Lin, Na-Sheng; Hsu, Yau-Heiu (Frontiers in Plant Science, 2022)
Plant argonautes (AGOs) play important roles in the defense responses against viruses. The expression of Nicotiana benthamiana AGO5 gene (NbAGO5) is highly induced by Bamboo mosaic virus (BaMV) infection; however, the underlying mechanisms remained elusive. In this study, we have analyzed the potential promoter activities of NbAGO5 and the interactions with viral proteins by using a 2000 bp fragment, designated as PN1, upstream to the translation initiation of NbAGO5. PN1 and seven serial 5'-deletion mutants (PN2-PN8) were fused with a β-glucuronidase (GUS) reporter and introduced into N. benthamiana genome by Agrobacterium-mediated transformation for further characterization. It was found that PN4-GUS transgenic plants were able to drive strong GUS expression in the whole plant. In the virus infection tests, the GUS activity was strongly induced in PN4-GUS transgenic plants after being challenged with potexviruses. Infiltration of the transgenic individually with BaMV coat protein (CP) or triple gene block protein 1 (TGBp1) revealed that only TGBp1 was crucial for inducing the NbAGO5 promoter. To identify factors responsible for controlling the activity of NbAGO5 promoter, we employed yeast one-hybrid screening on a transcription factor cDNA library. The result showed that NbNAC42 and NbZFP3 could directly bind the 704 bp promoter regions of NbAGO5. By using overexpressing and virus-induced gene silencing technique, we found that NbNAC42 and NbZFP3 regulated and downregulated, respectively, the expression of the NbAGO5 gene. Upon virus infection, NbNAC42 played an important role in regulating the expression of NbAGO5. Together, these results provide new insights into the modulation of defense mechanism of N. benthamiana against viruses. This virus inducible promoter could be an ideal candidate to drive the target gene expression that could improve anti-virus abilities of crops in the future.